ANALYSIS OF THE EFFECT OF STUDENTS’ SELF-CONFIDENCE ON SPEAKING SKILL - Kansil, Vriska Enggelina; Tuna, Jim R; Liando, Nihta V. F. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2022)
Based on the result of observation, there were still many students who had difficulty developing speaking skill because of the lack of self-confidence. This study aims to investigate whether students self-confidence affect’s their speaking skill or not. This study used qualitative correlation method with a questionnaire, and public speaking subject score (KHS), the population of this study is English Education department class of 2017. The sample of this study is students who taking a public speaking subject. Based on the result that has been carried out it can be seen that the percentage of answer choices agree on the factors that can affect students speaking skills have a high percentage of approval by the respondents, such as motivation to speak was approved by 100% of respondents. Then the factor that can affect students confidence gets a high percentage of approval by respondents such as you are worried about making mistakes was approved by 90% respondents. The percentage result from the effect of self-confidence on speaking skill respondents answered you speak well when you are confident approved by 93.30% of respondents. From the results of the student’s opinion it can be concluded that students speaking ability is influenced by self-confidence